Social inequalities in grip strength, physical function, and falls among community dwelling older men and women: findings from the Hertfordshire Cohort Study. - Syddall, H; Evandrou, M; Cooper, C; Sayer, A (2009)
Objectives. To explore social inequalities in grip strength, SF-36 physical functioning (PF), and falls among older people. Methods. We analyzed data from 3,225 men and women (age 59-73 years) who participated in the Hertfordshire Cohort Study, United Kingdom. Car availability and home ownership were used as markers of material deprivation. Results. A total of 6.4% of men (17.7% women) had no car and 19.3% of men (23.1% women) did not own their home. Having fewer cars was associated with lower grip and poorer PF among men and women (p < .001), and increased falls among men (p < .001). Not owning one's home was associated with lower grip in men and women (p < .001) and poorer PF in men (p < .001). Lower social class was associated with falls among women only (p = .01). Discussion. There are social inequalities in grip strength, PF, and falls among older people. Interventions should consider the contribution of social inequalities to the problem.